Effect of levels of farmyard manure and nitrogen fertilization on grain yield and use efficiency of nutrients in wheat (Triticurn aestivum) - Singh, Ravindra; Agarwal, S K (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was carried out during the winter seasons of 1996-97 and 1997-98 on sandy-loam soils of Hisar, Haryana, to study the effect of organic and inorganic sources of nitrogen on productivity, profitability, optimum dose of nitrogen and its use efficiency in wheat (Triticum aestivum L. emend. Fiori & Paol.). Application of recommended N, P and ZnSO4 (120 + 25 + 26.2 kg/ha) along with farmyard manure @ 10 tonnes/ha resulted in significantly higher grain yield (4 259 and 3653 kg/ha) than other treatment combinations. The combined effect of farmyard manure and N levels showed that the agronomic efficiency increased substantially (24.9 and 25.8) at 10 tonnes/ha farmyard manure along with 60 kg N/ha. Apparent recovery (69.3 and 70.1) and partial factor productivity of N (53.6 and 47.4) improved with increasing levels of farmyard manure up to 20 tonnes/ha at 60 kg N/ha. However, it decreased with increasing levels of N (180 kg/ha) at all the levels of farmyard manure, except at recommended N, P, ZnSO4 application. The results of combined effect of farmyard manure and N levels revealed that, the apparent recovery of N decreased from 35.5,56.6,69.3 and 74.6 at 60 kg N/ha to 23.5,32.1, 36.2 and 38.1 at 180 kg N along with 0, 10,20 and 30 tonnes farmyard manure/ha during 1996-97 respectively. Based on mean data, highest physiological efficiency of N (41.32 and 40.83), P (212.24 and 215.55) and K (38.82 and 40.98) was recorded at 60 kg N/ha during 1996-97 and 1997-98 respectively. The increasing levels of N from 60 to 180 kg/ha in combination with 30 tonnes/ha farmyard manure reduced the physiological efficiency of N, P and K by 4.71,9.6 and 10.0 during 1996-97 and 6.04, 26.8 and 2.39 during 1997-98 compared with the 60 kg/ha N along with 10 tonnes/ha farmyard manure. Maximum net returns of Rs 13966 with the benefit : cost ratio 2.31 was obtained at 20 tonnes/ha famiyard manure along with 180 kg/ha N during 1996-97 and Rs 12415 with benefit : cost ratio 2.17 at recommended fertilization during 1997-98.